1986
DOI: 10.1159/000233986
|View full text |Cite
|
Sign up to set email alerts
|

Limiting Dilution Analysis of Age- and Gender-Related Differences in Autoantibody Production against Bromelain-Modified RBC

Abstract: Cultured peritoneal cells from untreated mice, after 3 days of in vitro culture, produce autoantibodies against bromelain-treated isologous erythrocytes. The autoantibody response varies with both age and gender. The effects of age and gender were demonstrated by culturing peritoneal cells using limiting dilution techniques. In neonatal mice there were no precursor cells that differentiated into autoantibody secretors. Cells from female mice gave higher responses than cells from males, and the effect was more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
2
0

Year Published

1987
1987
1991
1991

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 10 publications
2
2
0
Order By: Relevance
“…In this study, we also addressed the ontogeny of anti-PtC lymphocytes using the direct enumeration of liposome-binding cells. Our observation of the appearance of PtC-binding cells shows a good correlation with studies of anti-BrMRBC PFC ontogeny (33,37). The increase in abundance of PtC-specific, Ly-l' cells during the first 3 wk of life does not result from an increase in the total Ly-l' B cell population .…”
Section: Discussionsupporting
confidence: 83%
“…In this study, we also addressed the ontogeny of anti-PtC lymphocytes using the direct enumeration of liposome-binding cells. Our observation of the appearance of PtC-binding cells shows a good correlation with studies of anti-BrMRBC PFC ontogeny (33,37). The increase in abundance of PtC-specific, Ly-l' cells during the first 3 wk of life does not result from an increase in the total Ly-l' B cell population .…”
Section: Discussionsupporting
confidence: 83%
“…The results presented here show that it enhances normal Ly-1 B cell antibody responses including secretion of autoantibodies. Others have shown that a proportion of peritoneal B cells, similar to that measured here, spontaneously secrete autoantibody [39], that this secretion is enhanced by SN from EL4 thymomas [27] and that most peritoneal B cell autoantibody secretion to BrMRBC and some other autoantigens is due to Ly-1 B cells [20,411. Here these observations are brought together and, more importantly, identify IL 5 as one of the agents responsible for enhancing Ly-1 B cell autoantibody secretion in vitro.…”
supporting
confidence: 80%
“…PFC responses to TNP-SRBC were performed in agarose using TNP-SRBC prepared as described by others [38] and guinea pig C (Gibco). Anti-bromelain-treated mouse red blood cell (BrMRBC) PFC were assayed in situ according to the method of others [39] using MRBC which had been treated for 45 min at 37°C with 20 mg/ml of bromelain (Fluka, Buchs, Switzerland) using equal volumes of packed cells and bromelain/PBS solution.…”
Section: Antibody Secretionmentioning
confidence: 99%
“…Uncultured spleen cells and cells harvested from 96-well plates were assayed according to the method of Cunningham and Szenberg [15], The assay procedure for cells cultured in Terasaki trays has been described elsewhere [ 18].…”
Section: Assay For Autoantibody Productionmentioning
confidence: 99%